PENGARUH RASIO AKTIVITAS TERHADAP PROFITABILITAS PADA PT. MAYORA INDAH, TBK - Fadhilah, Nurul; Muhlis, Muhlis; Jaenab, Jaenab (Jurnal Manajemen, 2024)
This research aims to determine the effect of activity ratios on profitability at PT. Mayora Indah, Tbk. This type of research is associative. The research instrument used is a list of tables consisting of sales data, total assets, cash at the beginning of the year, cash at the end of the year, average cash, total fixed assets and net profit at PT. Mayora Indah, Tbk for 10 years, namely from 2013 to 2022. The population in this research is the financial statements of PT. Mayora Indah, Tbk has been listed on the IDX from 1990 to 2022, which is 23 years. The sample in this research is the financial report of PT. Mayora Indah, Tbk for 10 years, namely from 2013 to 2022. The sampling technique used in this research was purposive sampling. Data collection techniques use documentation and literature study. The sata analysis technique uses the t test and f test. The research results show that Total Asset Turnover (TATO), Cash Turnover (CTO) and Fixed Asset Turnover (FATO) influence Return On Assets (ROA) at PT. Mayora Indah, Tbk.